Wireless control system for real-time logging of vehicle's emission - Yin, Dong (2015)
Smoking is a problem plaguing the world which causes lots of deaths with some smoking-related diseases every year. And the second-hand smoke also can cause diseases which has the similar effect as direct smoking. In order to protect the public and stay away from cigarette smoke, many countries and regions implemented various smoking ban laws. In addition, monitoring smoking in public areas has become a big problem due to the high cost of cigarette smoke sensors and also the poor monitoring performance of general smoke sensors. This project is carried on to design a low-cost cigarette smoke sensor which consists of three different kinds of sensors. To achieve this aim, there are three parts of the project that need to be fulfilled. The first part is to select three suitable sensors for this project which cost less than the current cigarette smoke sensor and can work together well. The second part is to analysis the error caused by these sensors. With data from technical datasheets and simulating tolerances, the errors inherent to each sensor are compensated to meet the demand of a marketable product and to ensure its safety. The third part of this project is to extend this project for other purposes such as detecting fire, and monitoring of harmful automobile exhaust. Therefore, the objective of this project is to select three sensors and provide simulation evidence that they can work together to provide a low cost, high precision, and multifunction smoke sensing system that can primarily detect cigarette smoke.